Primary care consultations for respiratory tract symptoms during the COVID-19 pandemic: a cohort study including 70, 000 people in South West England. (11th October 2021) - Dambha-Miller, Hajira; Hounkpatin, Hilda O; Morgan-Harrisskitt, Jeffrey; Stuart, Beth; Fraser, Simon D S; Roderick, Paul
Abstract: Background: Primary care consultations for respiratory tract symptoms including identifying and managing COVID-19 during the pandemic have not been characterized. Methods: A retrospective cohort analysis using routinely collected records from 70, 431 adults aged 18+ in South England within the Electronic Care and Health Information Analytics (CHIA) database. Total volume and type of consultations (face-to-face, home visits, telephone, email/video, or out of hours) for respiratory tract symptoms between 1 January and 31 July 2020 (during the first wave of the pandemic) were compared with the equivalent period in 2019 for the same cohort. Descriptive statistics were used to summarize consultations by sociodemographic and clinical characteristics, and by COVID-19 diagnosis and outcomes (death, hospitalization, and pneumonia). Results: Overall consultations for respiratory tract symptoms increased by 229% during the pandemic compared with the preceding year. This included significant increases in telephone consultations by 250%, a 1, 574% increase in video/email consultations, 105% increase in home visits, and 92% increase in face-to-face consultations. Nearly 60% of people who presented with respiratory symptoms were tested for COVID-19 and 16% confirmed or clinically suspected to have the virus. Those with complications including pneumonia, requiring hospitalization, and who died were more likely to be seen in-person. Conclusion: During the pandemic, primary care substantially increased consultations for respiratory tract symptoms to identify and manage people with COVID-19. These findings should be balanced against national reports of reduced GP workload for non-COVID care.